KONSEP PENDIDIKAN KARAKTER ANAK MENURUT ISLAM - Sariyulis Sariyulis (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2022)
The character of children these days makes many people worried. Society hopes to make a child or individual with good character, noble character, and able to live his life in accordance with Islamic guidance. To achieve this, an in-depth study is needed to obtain maximum and expected results. This study uses a qualitative-descriptive research method with literature study techniques. The results of this study obtained data and facts that character education from an early age is very important, by choosing the right methods according to Islamic teachings so that children become human beings who are educated in faith, science, charity, have broad insight, become good citizens, and noble character that can be beneficial for all mankind.Keywords: Islamic, education, character